Relevansi Cerita Lisan Dumadine Gunung Kelud pada Tradisi Larung Sesaji di Kabupaten Kediri - Ferdian Permana; Rahma Ari Widihastuti (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
The oral story of the Legend of Mount Kelud in Kediri Regency has several variations from each speaker with various backgrounds. Apart from the various versions that have appeared, the oral story is believed to have a connection with the tradition of larung sesaji held on Mount Kelud. The purpose of this study was to collect the oral stories of Dumadine Gunung Kelud in Kediri Regency and then to analyze their relevance to the tradition of larung sesaji. In this study used a qualitative research design with an ethnographic approach. The results of oral stories found in the field were then analyzed using the theory of oral literature from Ruth Finnegan. The research location is located in Kediri Regency with Sugihwaras Village as the main location for collecting data in the study. Collecting data in this study using interview techniques, observation, and documentation. The results of the research show that there are three variations of the Dumadine Gunung Kelud oral story in Kediri Regency which are still in spoken form and have not been inventoried in written form. These variations with differences in content were told by Mbah Suparlan, Pak Eko Priatno, and Nur Isriyatin. The three stories are different in terms of intrinsic elements and different compositions. Even though the composition of the story is different, it still contains the same pattern. This research also shows that this story is the basis of the larung offering ritual held on Mount Kelud. Keywords: folklore;oral stories;traditions;larung sesaji;mountain kelud